Heurística de usabilidad y su aplicación al web site del Gobierno Autónomo Descentralizado provincial de Los Ríos. - Figueroa Moran, Félix Alexander (2024)
This research focuses on the Decentralised Autonomous Government of the Province of Los Ríos, which faces serious problems in the use of its website, vital for the effective dissemination of information and government services. The current platform has aesthetic and functional flaws that affect the user experience, such as responsive design problems and unintuitive navigation on mobile devices. To address this problem, the use of Jakob Nielsen's usability heuristics is proposed as an evaluation method, thus fulfilling the overall objective of increasing user engagement and satisfaction by comprehensively identifying and diagnosing usability issues, specific objectives include identifying specific vulnerabilities, analysing appropriate heuristics and recommending specific site improvements. Lack of adequate usability was found to be a major barrier to effective citizen participation on local government digital platforms, improving usability will not only benefit the current user experience, but will also set the standard for future public platforms that meet the requirements set out in the Organic Law on Transparency and Access to Public Information (LOTAIP).